Finding Patristic Authorities in the Carolingian Period (Interfaces: A Journal of Medieval European Literatures, 2024)
This article investigates how and for what reasons Carolingian scholars sought and found works by the so-called church fathers. It begins by discussing the use of late antique bibliographical guides to learn about patristic titles and their orthodoxy. It looks at how Carolingian scholars went about acquiring copies of interesting works through their networks, and the peculiarities particular to the search for patristic texts. It closes by looking at examples of how some of the works of Augustine of Hippo were 'edited' by Carolingian scholars, arguing that such active engagement with these texts took place more often than sometimes thought.
Keywords: Carolingians; Manuscripts; Patristics; Medieval editing; Annotations